Natural Sources of Drugs for Neurodegenerative Diseases - Prajapati C.; Rai S.N.; Mishra S.S.; Singh S.K.; Singh A.K. (My University, 2025)
Neurodegenerative diseases involve gradual breakdown and eventually death of nerve cells. Neurodegenerative disorders lack an effective therapy because the central nervous system’s neurons have a limited capacity for regeneration. There are many different causes of neurological illnesses, such as congenital anomalies, genetic disorders, autoimmune diseases, infections, and environmental or lifestyle-related health issues. Endophytes are a group of microorganisms that thrive within host plants without apparently harming them. Both plant-based bioactives and fungal endophyte-based bioactives exhibit neuroprotective activities. Antioxidant activity, anti-amyloid aggregation, anti-inflammatory, monoamine modification, and inhibition of acetylcholinesterase are some of the mechanisms by which plant-based bioactives exhibit neuroprotective activities. Ongoing research focuses on the neuroblastic cell regeneration approach to treat neurodegenerative disorders. Peptides, cytokines, and polyphenolic antioxidants have regenerative capacity and thus can be used to treat neurodegenerative diseases. Over 60 million people suffer from these incurable diseases worldwide as a result of the rapidly aging society. As a result, finding novel medications and therapeutic approaches has become a crucial study area. This chapter focuses on the efficacy of natural compounds derived from plants and associated microbes towards neurodegenerative disorders. © 2025 selection and editorial matter, Sachchida Nand Rai, Sandeep Singh, Santosh Kumar Singh.